NANOCRINOLOGY - Sanjay Kalra; Saptarshi Bhattacharya; Atul Dhingra (Journal of the Pakistan Medical Association, 2023)
We conceptualize and define nanocrinology as the science that studies the nanometric and subnanometric precision that operates in diagnostic and therapeutic endocrinology. It includes advanced generation assays, which can detect low concentrations of hormones, and modern drug delivery systems that allow more efficient delivery of endocrinotropic agents. Nanocrinology is a rapidly growing field of endocrinology, and we call for greater research and adoption of this science. Keywords: Diagnosis, endocrinology, hormone, radioimmunoassay, nanoformulation.